Some Recent Developments in Structures Fitted with Buckling Restrained Braces (BRBs) - Guerrero, Hector; Escobar José Alberto (Academia XXII, 2018)
The authors have conducted several numerical and experimental studies aimed at quantifying the bene ts of Buckling-Restrained Braces (BRBs) when tted in frame structures. The most signi cant experimental stud- ies include shaking table tests on three building models made of concrete or steel. Among the numerical studies are: 1) the proposal of a seismic design method; 2) an evaluation of the economic bene ts of BRBs; 3) studies on the residual displacement of structures equipped with BRBs; and 4) the response of structures equipped with BRBs when subjected to seismic aftershocks. This paper presents a summary of the identi ed bene ts of BRBs for frame structures with the intention of encouraging their use in earthquake zones.